Penggunaan Bakteriosin yang Diproduksi oleh Lactobacillus plantarum sebagai Pengawet Alami untuk Daging Ayam yang Disimpan di Suhu Ruang - Y. Nurraifah; I. I. Arief; N. Ulupi (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2021)
Bacteriocins is a natural preservative (bio-preservatives) that can safely be used for food. Bacteriocinscan be produced by a group of Lactic Acid Bacteria (LAB). Several strains of lactic acid bacteria (LAB)is bactericidal against gram positive and gram negative bacteria. The purpose of this study was toanalyze the bacteriocins produced by Lactobacillus plantarum in chicken meat and determine the levelof the last and long-term. Factors that are seen in this study is the levels of bacteriocins and also theduration of storage of chicken meat. The levels of bacteriocins is 0% and 10% by way of spraying inchicken meat and duration of storage are at 0, 5, 10, 15, 20, and 25 hours at room temperature. Thisstudy used a factorial completely randomized design with three replications. Plantaricin concentrationagainst pH and aw values were significantly different (P<0.05). The test result of storage duration againstwater content were significantly different (P<0.05). Treatment of plantarisin IIA-1A5 10% to maintainthe condition of chicken meat was better than treatment without the adding plantarisin.